Analisis Efektivitas Kerja Style Attendant di Hotel X: Mengatasi Tantangan Kuantitas Kerja untuk Pelayanan Optimal - Arthini, Ni Nyoman Suci; Merta, I Nyoman Putra Arta; Iswarini, Ni Ketut (Journal of Hospitality Accommodation Management (JHAM), 2025)
This research was motivated by guest complaints regarding the lack of thoroughness of Style Attendants in carrying out their duties in the Style Department of Hotel X. This study aims to evaluate the work effectiveness of Style Attendants based on three indicators from Hasibuan's theory: work quality, work quantity, and time utilization. Data were collected through interviews and documentation involving three Style Attendants and one team leader. The data analysis technique used in the research is descriptive qualitative. The study's results showed a decrease in effectiveness in the work quantity and time utilization indicators due to excessive additional workloads on runners. However, in the work quality indicator, Style Attendants could complete tasks well and on time. This study is expected to be a basis for increasing the effectiveness of Style Attendants, especially in terms of work quantity, to provide more optimal service to guests.